Co-Inoculation and Sulfur Fertilization in Soybeans - L. H. Moro Rosso; A. F. de Borja Reis; S. L. Naeve; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2021)
Soybeans [Glycine max(L.) Merr.] rely on large nutrient uptake, especially nitrogen (N), to produce seeds with high nutritional value. Biological N fixation (BNF) supplies most of the plant N demand and enhancement of this process might improve cropping systems’ sustainability. Although seed inoculation withBradyrhizobiumspp. for soybean crop is a well-known management practice, co-inoculation with the freeliving N-fixerAzospirillum brasilensehas not been deeply investigated in the US, to our knowledge. Thus, this research explores the effect of co-inoculation withA. brasilenseon soybean yield and seed nutritional quality (protein, oil, essential and sulfur (S) amino acids concentration) under contrasting fertilizer S rates. Two-way factorial experiments were conducted in Manhattan and Topeka (KS, US) during the 2019 growing season. Sulfur rates of 0 and 20 lb/a were combined with four inoculation strategies: 1) non-inoculated, 2) seed inoculation withBradyrhizobium japonicum, 3)A. brasilense, and 4) co-inoculation using both bacteria. The proportion of BNF was estimated via the relative abundance of ureide-N (RAU) at the R5 stage (beginning seed filling). Shoot dry mass was also assessed at R5, as well as seed yield and seed size (1000-seed weight) at harvest time (R8 stage). Dry basis concentration of seed components was also determined (protein, oil, essential and sulfur amino acids). None of the treatment factors significantly (P<0.05) influenced any observed trait. Overall, RAU averaged 80%, seed yield 65 bu/a, protein 42%, and oil 20%. Future research is necessary to eventually capture effects from co-inoculation and S fertilization in soybeans.
Keywords: nitrogen fixation; protein; amino acids; sulfur